2017
DOI: 10.1038/s41371-017-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, treatment, and control in northeast China: a population-based cross-sectional survey

Abstract: Hypertension has been recognized as a major risk factor for cardiovascular disease. We aimed to analyze the current prevalence, awareness, treatment, and control of hypertension in northeast China. This cross-sectional survey adopted the multistage stratified random cluster sampling method to obtain a representative sample of adults aged 40 years or older in the general population of northeast China. Hypertension was defined as a systolic blood pressure (SBP) ≥ 140 mm Hg, or diastolic blood pressure (DBP) ≥ 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
6
13
0
Order By: Relevance
“…For example, our estimated hypertension prevalence (18.3%) is much lower than the national average 57.3% (Zhang et al , 2017), probably simply due to successful and widely available treatment. Individuals who were previously diagnosed with hypertension and comply with the prescribed medication may not show any symptom (high blood pressure) in the physical examination.…”
Section: Results and Interpretationsmentioning
confidence: 59%
“…For example, our estimated hypertension prevalence (18.3%) is much lower than the national average 57.3% (Zhang et al , 2017), probably simply due to successful and widely available treatment. Individuals who were previously diagnosed with hypertension and comply with the prescribed medication may not show any symptom (high blood pressure) in the physical examination.…”
Section: Results and Interpretationsmentioning
confidence: 59%
“…This is in line with the result of zhang’s et al . (2017), reporting that hypertensive people with a family history of coronary heart diseases were more likely to have controlled hypertension 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Although serial national surveys showed that the burden of hypertension increased dramatically over the past decade in China, the situation in northeast China seems more serious 7,8. Previous assessments of hypertension in northeast China are limited due to small or unrepresentative sample size, or insufficient estimation of related risk factors, particularly in urban areas 9,10. Furthermore, previous studies reported the steeper increase in prevalence of hypertension both in urban and rural areas in other countries;11,12 however, the current characteristics of hypertension as well as related risk factors in urban and rural areas of northeast China have not been well studied, and are still lacking.…”
Section: Introductionmentioning
confidence: 99%